A nationwide survey on awareness and knowledge about Bronchial Provocation Test amongst doctors in Malaysia - Ng, khai Lip; Huan, Nai Chien; Mohammad, Fatimah Azmah; Mohd Aminudin, Nur Husna; Muhammad, Fatimah A'tirah; Abdul Rahaman, Jamalul Azizi (European Respiratory Society, 2021)
Background: Bronchial provocation test (BPT) is widely used internationally not only to evaluate bronchial responsiveness in conditions especially asthma, but is also utilized as a marker of control, severity and prognosis for asthma. However, the uptake of BPT in certain countries including Malaysia remains low. We aimed to explore this lack of knowledge by assessing the current level of awareness and knowledge on BPT amongst doctors in Malaysia. Materials and methods: A nationwide web-based questionnaire targeting doctors was sent through social media (Facebook, WhatsApp and Telegram) and Malaysian Medical Association (MMA) mailing lists between 1 October 2020 - 5 February 2021. Results: In all 415 survey responses were analysed from doctors of various grades namely medical officers to consultants. A total of 404 (97.35%) encountered patients with asthma in their daily practice. According to specialty: 169 (40.72%) were from primary care, 121 (29.16%) internal medicine, 50 (12.05%) pulmonary medicine and 75 (18.07%) others. Only 163 (39.28%) were aware of BPT as a tool to diagnose asthma. 232 (55.90%) and 124 (29.88%) regarded BPT as an important test and felt confident to refer patients for BPT respectively. Of those participants who were not confident to refer: 35.17% were unsure of BPT indications, 33.21% were unsure of centres providing BPT, 8.17% cited logistic reasons, 6.04% were concerned of possible BPT side effects. 387 (93.25%) wanted more training in BPT. The median BPT knowledge score was 20% (1 out of 5). Awareness and knowledge were affected by specialty but not by: region of practice, gender, age and grade from logistic regression analysis. Conclusion: Various national level programs and targeted local interventions are much needed to increase the awareness, knowledge and uptake of BPT in Malaysia.